The heads of religious houses, England and Wales, I: 940-1216 - Knowles, David; Brooke, Christopher Nugent Lawrence; London, Vera C. M. (Cambridge University Press, 2001)
This is the first of two volumes, now covering the heads of religious houses in England and Wales from the tenth-century reform to the death of Edward III, 940–1377. This first volume, by the great master of monastic history, Dom David Knowles, aided by Christopher Brooke and Vera London, was published first in 1972 and was quickly recognised as a major work of reference, noted for its mastery of accurate detail. It has now been brought up to date with substantial addenda and corrigenda by Christopher Brooke. The 1972 volume covers the period 940–1216, and comprises fully documented, critical lists of monastic superiors, with succinct biographical details. It is an essential foundation for all prosopographical study of the religious history of the period; and the precise chronology that it underpins is invaluable for dating innumerable undated documents. As such, the book is a fundamental tool of medieval research.